Correlation of Breed, Growth Performance, and Rumen Microbiota in Two Rustic Cattle Breeds Reared Under Different Conditions - Daghio, Matteo; Ciucci, Francesca; Buccioni, Arianna; Cappucci, Alice; Casarosa, Laura; Serra, Andrea; Conte, Giuseppe; Viti, Carlo; McAmmond, Breanne M.; Van Hamme, Jonathan D.; Mele, Marcello (Frontiers in Microbiology, 2021)
The use of rustic cattle is desirable to face challenges brought on by climate change. Maremmana (MA) and Aubrac (AU) are rustic cattle that can be successfully used for sustainable production. In this study correlations between two rearing systems (feedlot and grazing) and the rumen microbiota, the lipid composition of rumen liquor, and the growing performance of MA and AU steers were investigated. Bacterial community composition was characterized by high-throughput sequencing of 16S rRNA gene amplicons, and the rumen liquor lipid composition was determined by measuring fatty acid and the dimethylacetal profiles. The main factor influencing bacterial community composition was the cattle breed. Some bacterial groups were positively correlated to average daily weight gain for the two breeds (i.e., Rikenellaceae RC9 gut group, Fibrobacter and Succiniclasticum in the rumen of MA steers, and Succinivibrionaceae UCG-002 in the rumen of AU steers); despite this, animal performance appeared to be influenced by short chain fatty acids production pathways and by the presence of H2 sinks that divert the H2 to processes alternative to the methanogenesis.